Legal Dimension in Waqf Governance: The Role of Compliance Mediation in The Influence of Human Resources Quality and Supervision on The Accountability of Waqf Institutions - Grandis Imama Hendra; Nur Asnawi; Vivin Maharani Ekowati (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the role of compliance mediation in influence of human resource (HR) quality and supervision on accountability of waqf institutions registered with the Indonesian Waqf Board (BWI). This study provides insight into how these factors interact to improve institutional accountability, which is an important element in maintaining public trust in waqf management. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data were collected through a survey of 164 respondents consisting of stakeholders and practitioners at the Waqf Nadzir Institution. This model evaluates the direct and mediation relationships between variables. The results of the study indicate that the quality of human resources does not have a significant direct effect on the accountability of waqf institutions or on compliance. In contrast, supervision has a positive and significant effect on compliance and accountability. Compliance is proven to only mediate the relationship between supervision and accountability, but cannot mediate the relationship between the quality of human resources and accountability. This finding emphasizes the importance of effective supervision in improving institutional compliance and accountability. The quality of human resources in waqf institutions needs to be considered to improve the accountability of waqf institutions. The novelty of this study is to develop a theory of legitimacy in terms of the need for supervision in improving the accountability of waqf institutions mediated by waqf institution compliance.